The Efficacy of Supportive Peri-Implant Therapies in Preventing Peri-Implantitis and Implant Loss: a Systematic Review of the Literature - Ausra Ramanauskaite; Tellervo Tervonen (eJournal of Oral Maxillofacial Research)
Objectives: To study the efficacy of supportive peri-implant therapies in preventing clinical and radiological signs of peri-implantitis and implant loss.